1979
DOI: 10.1177/030089167906500507
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Medroxyprogesterone Acetate (MPA) Treatment in Advanced Breast Cancer. A Review

Abstract: Medroxyprogesterone acetate (MPA) when employed at high doses (greater than or equal to 500 greater than or equal to 1000 mg/day i.m.) can produce objective remission with improved survival in about 30% of postmenopausal women with advanced breast cancer resistant to cytotoxic drugs and endocrine therapies. When administered to women not previously treated with chemotherapy, the objective remission response rate reached 40%. From available evidence, high dose MPA can be considered a useful agent in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…In addition to a high response rate of approximately 40%, medroxyprogesterone acetate (MPA) treatment as an endocrine therapy is more likely to be effective in ER(–) cases than other endocrine therapeutic agents in recurrent or advanced breast cancer, holding an important position as first- and second-line therapy [1, 2, 3, 4]. Further, the accessory effects of MPA such as appetite stimulation, improvement in performance status (PS) and bone marrow protection are advantageous for many recurrent cases, and may lead to more frequent use of MPA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a high response rate of approximately 40%, medroxyprogesterone acetate (MPA) treatment as an endocrine therapy is more likely to be effective in ER(–) cases than other endocrine therapeutic agents in recurrent or advanced breast cancer, holding an important position as first- and second-line therapy [1, 2, 3, 4]. Further, the accessory effects of MPA such as appetite stimulation, improvement in performance status (PS) and bone marrow protection are advantageous for many recurrent cases, and may lead to more frequent use of MPA.…”
Section: Introductionmentioning
confidence: 99%
“…Enomoto et al [15]reported that the response rate of MPA 1,200 mg was somewhat superior to 600 mg but there were no significant differences between the two doses in combination with cyclophosphamide and epirubicin. Ganzina [16]reported that the response rate in patients treated with MPA at 200 mg or less was 17% and thus concluded that so-called ‘low dose MPA therapy’ cannot achieve a satisfactory response rate. However, ‘high dose MPA therapy’ using higher doses appears to produce no marked difference in the response rate of different doses.…”
Section: Discussionmentioning
confidence: 99%
“…Progestin treatment of advanced breast cancer has been thought to be of age for several years [18]. However, recently route of administration and dosage have again been scrutiniz ed and these questions can no longer be regarded as solved [33].…”
Section: Progestins a N D A Ntiprogestinsmentioning
confidence: 99%